Sexual activity and the adolescent with haemophilia - Banchev, Atanas (Acta Biomedica Atenei Parmensis, 2023)
Haemophilia A and B are congenital bleeding disorders, associated with joint and soft tissue bleeding episodes. Adolescence is an important period of the individual development, associated with tendency to risky behavior in those, who suffer chronic conditions. The current review focuses on sexual health in the adolescents with haemophilia and related to sexual activity complications in the course of the disease such as iliopsoas hemorrhage and joint bleedings, models and strategies for sexual health promotion and education in this specific age group and disorder. (www.actabiomedica.it)